2019
DOI: 10.15386/mpr-1520
|View full text |Cite
|
Sign up to set email alerts
|

Oral health related quality of life and self-esteem in a general population

Abstract: Background and aims. The interest in the research of both Oral Health Related Quality Of Life and dental aesthetics has increased in the recent years. The aim of the current study consists in the evaluation of the perception of oral-health, dental aesthetics and self-esteem in a general population. Methods. A group of students of the Faculty of Dental Medicine, Cluj-Napoca, were trained in the field of questionnaire interviewing. The students were asked to apply the following questionnaires to a number of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Other studies have also confirmed that the concern of an individual with good appearance is generalized in any society. 24,25 Consistent with previous studies, 26,27 statistical associations were found between gender and impact on quality of life, with the girls presenting 2.54 times more chances of having an impact than boys. Girls, usually, are more sensitive to the perception of their own appearance than boys, 26,28 present more attention, perception and appreciation of with own oral health.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other studies have also confirmed that the concern of an individual with good appearance is generalized in any society. 24,25 Consistent with previous studies, 26,27 statistical associations were found between gender and impact on quality of life, with the girls presenting 2.54 times more chances of having an impact than boys. Girls, usually, are more sensitive to the perception of their own appearance than boys, 26,28 present more attention, perception and appreciation of with own oral health.…”
Section: Discussionsupporting
confidence: 85%
“…24,25 Consistent with previous studies, 26,27 statistical associations were found between gender and impact on quality of life, with the girls presenting 2.54 times more chances of having an impact than boys. Girls, usually, are more sensitive to the perception of their own appearance than boys, 26,28 present more attention, perception and appreciation of with own oral health. 26 However, it should be noted that in some researches this association was not found.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The best way to overcome the difficulties of lack of access to dental care for Special Needs Patients (SNP), is to make their caregivers aware of the impact that the benefits of oral health can have on their quality of life (DeMattei et al, 2012). However, it is necessary that the caregiver also know the importance of maintaining their own oral health (Grecu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, when it comes to awareness of oral hygiene, access to information is not yet so widespread, causing an impact on the individual's quality of life (Naseem et al, 2016). We know that oral health can contribute to health improvement generally, self-esteem and social integration (Grecu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%